The Risk Factors of Coronary Disorders in the Elderly - Ali Akbar Abdollahi; Seyyed Abedin Hosseini; Aref Salehi; GholamReza Vaghari; Naser BehnamPour (Golestan University of Medical Sciences, 2013)
Background and objective: Cardiovascular disease is the leading problem of the elders. It is progressive disorder that is initiated in childhood and its clinical demonstration is revealed after middle-‌aged period. This study aimed to determine the relationship between coronary artery disease- related risk-factors and aging. Material and Methods: This‌ ‌descriptive‌-‌analytical study was conducted on all 772 elders referring to Kosar Angiography Center in Golestan province, 2008-‌2009. The subjects were divided into coronary disorder group and normal group. The risk factors including age, gender, body mass index (BMI), blood pressure, diabetes mellitus, smoking and drug addiction were assessed. The data was analyzed by SPSS‌-16, using Mann-Whitney and T-test. Results: Most of the subjects were between 65 to‌ 75 years. Of the three main vessels, the most involved one‌ was circumflex (31.5%). ‌The factors such as gender and systolic hypertension were significantly different in two groups. Furthermore, the Risk ratio in the patients with ‌systolic hypertension (1.13 times) and the ones with diastolic hypertension (1.11 times) was more than normal group. Conclusion: Gender and systolic hypertension in the elders with CAD are the main and predisposing factors. Therefore, if we control hypertension, it may be possible to prevent from the CAD progress.